MEKANISME REKRUITMEN CALON BUPATI DALAM PEMILIHAN UMUM KEPALA DAERAH SECARA LANGSUNG TAHUN 2015 DI KABUPATEN LAMPUNG SELATAN - Emiraldo Win Pazqara (Jurnal Penelitian Ilmiah INTAJ, 2018)
The purpose of this research was to know the recruitment process performed by National Mandate Party in recruiting Government Regent candidate in the general election of district head directly in South Lampung at 2015. Method used in this research was qualitative experiment method with interactive analysis. Result of the research based on interview, observed documentation files, and the rule of law as guided in recruitment process by National Mandate Party South Lampung, showed that recruitment process at National Mandate Party was open with several indicators: (1) open candidacy for public in other words there is no party cadre monopoly; (2) several candidates were socialized in order to get response and idea from public; (3) selected candidates were established through convention democratically and can be accepted by society. Keywords: Recruitment, Government Regent, South Lampung